Academic discourse socialization case study on multilingual learners - Fujieda, Yutaka, 1975- (Lexington Books, 2022)
"In this book, Yutaka Fujieda illustrates how multilingual learners extend substantial efforts to tackle academic discourses and navigate their academic identities. This book provides profound insights into the processes and practices of academic literacy socialization in various learning contexts"--